Pendampingan Hukum Preventif bagi Pekerja Tambang Mengenai Hak-Hak PHK di Maluku Utara - John Mid Rais Arihi; Hamrin Hamrin (Universitas Muhammadiyah Mataram, 2026)
Abstract: Employment termination in the mining sector often creates legal problems due to workers' limited understanding of their statutory rights and industrial dispute resolution mechanisms. This community service program aimed to improve the legal awareness and understanding of mining workers in North Maluku regarding post-termination rights through preventive legal assistance. The program adopted a participatory legal empowerment approach consisting of preparation, needs assessment, legal counseling, Focus Group Discussion (FGD), industrial dispute settlement simulation, individual legal consultation, evaluation, and follow-up activities. Program effectiveness was assessed using pre-tests, post-tests, observations, and participant satisfaction questionnaires. The results demonstrated that the preventive legal assistance program significantly improved participants' legal literacy, with an average increase in understanding of 48.6%, from an initial score of 41.2% to 89.8% after the program. In addition to strengthening participants' knowledge of employment termination rights and industrial dispute settlement procedures, the program also enhanced communication, discussion, negotiation, and problem-solving skills in industrial relations. These findings indicate that preventive legal assistance based on community participation effectively strengthens workers' legal capacity while fostering harmonious, productive, and equitable industrial relations.Abstrak: Pemutusan hubungan kerja (PHK) pada sektor pertambangan berpotensi menimbulkan permasalahan hukum akibat masih rendahnya literasi hukum pekerja mengenai hak-hak normatif dan mekanisme penyelesaian perselisihan hubungan industrial. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan pemahaman dan kesadaran hukum pekerja tambang di Provinsi Maluku Utara mengenai hak-hak setelah PHK melalui pendampingan hukum preventif. Metode yang digunakan adalah pendekatan participatory legal empowerment yang dilaksanakan melalui tahapan persiapan, identifikasi kebutuhan, penyuluhan hukum, Focus Group Discussion (FGD), simulasi penyelesaian perselisihan hubungan industrial, konsultasi hukum individual, evaluasi, dan tindak lanjut. Evaluasi dilakukan menggunakan pre-test, post-test, observasi, dan angket kepuasan peserta. Hasil kegiatan menunjukkan bahwa pendampingan hukum preventif mampu meningkatkan literasi hukum pekerja dengan rata-rata peningkatan pemahaman sebesar 48,6%, dari nilai awal 41,2% menjadi 89,8%. Selain meningkatkan penguasaan terhadap hak-hak pekerja dan prosedur penyelesaian perselisihan hubungan industrial, kegiatan ini juga memperkuat kemampuan peserta dalam berkomunikasi, berdiskusi, dan menyelesaikan permasalahan hubungan industrial secara dialogis. Program ini berkontribusi dalam membangun budaya hukum yang mendukung terciptanya hubungan industrial yang harmonis, produktif, dan berkeadilan.